Peasant Reform of 1861 in Reflection of Regional Press (“Vyatskiye Gubernskiye Vedomosti”) - A. M. Subbotina (Научный диалог, 2021)
The question of how the abolition of serfdom in 1861 was covered in the Russian regional press is considered in the article. The novelty of the research lies in the fact that, using the example of “Vyatskiye Gubernskiye Vedomosti”, it is shown how publications about the peasant reform changed in 1861—1911. The conclusion is made about the importance of regional official publications for the formation of public opinion, which contributed to the transformation. The greatest attention is paid to publications of the 1860s, since it was during this period that the newspaper showed the greatest interest in the reform, which needed public support. The author notes that on the pages of “Gubernskiye Vedomosti” a variety of materials were published on the abolition of serfdom. They performed the functions of informing, popularizing transformations, establishing interaction with the public, and others. It is shown that the Manifesto of February 19, 1861, the circulars of the Ministry of Internal Affairs on peasant affairs, extracts from the journals of the “provincial presence on peasant affairs” informed the population about the progress of the reform, presenting ways to resolve the arising problems. It is concluded that the news and journalistic articles demonstrated an expression of loyal gratitude to Alexander II the Liberator from various strata of the population, especially peasants.